Salo [videorecording (DVD)] : or the 120 days of Sodom - Bonacelli, Paolo, 1939-; Cataldi, Giorgio; Valletti, Aldo; Boratto, Caterina (The Criterion Collection, 2008)
A transposition of the Marques de Sade's eighteenth century opus of torture and degradation to 1944 Fascist Italy. A thought-provoking inquiry into the political, social, and sexual dynamics that define the world we live in. Special features included.